The Eucharist as a Sacrament Integrating the Family (Under Canon Law) - Zbigniew Janczewski (Kościół i Prawo)
The Eucharist is the source and top of the Christian life. This article analyzes the regulations of canon law related to participation in the Eucharist and receiving holy communion by the family. The author aims to show how such activities affect the unification of the entire family community, spouses, their children, and even grandparents. The first part discusses the Eucharist as the sacrament of unity. The next one discusses the family’s partaking in holy communion. The last one shows the role of the sacrament in the life of mixed marriages and marriages between individuals of different Catholic rites.